The Participation Budgeting and responsibility accounting in Effectiveness of Cost Control at the Department of Highways and Construction Development of Prince North Sumatra - Retnawati Siregar; Linda Lores; Ali Usman; Rahma Darni Daulay (VALUE, 2022)
This study aims to determine the effect of budgetary participation and accountability accounting on the effectiveness of cost control at the Department of Highways and Construction of North Sumatra Province. This type of associative research. The research population is all divisions of the Department of Highways and Construction of North Sumatra Province. Sampling used the purposive sampling method with a total sample of 30 budget drafting teams including financial staff, heads of sub-sections, heads of divisions, and heads of the internal control unit of the Department of Highways and Construction of North Sumatra Province. The research method uses associative research with data processing using SPSS software. The results showed that budgeting participation had a positive and significant effect on the effectiveness of cost control. Responsibility accounting has a positive and significant effect on cost control. Participation in budgeting and accountability accounting has a positive and significant effect on the effectiveness of cost control. Effectiveness of cost control to see the role of company functionaries in coordinating ongoing activities and performance will run more effectively and efficiently and run optimally which of course has a good influence on the continuity of the organization in order to achieve a goal